Pedagogical and Physiological Peculiarities of Construction of Educational and Training Sessions with Girls 15-17 Years Old - Djalolov Sherzod Valievich; Khudieva Sabina (Genius Journals, 2023)
To study the level of physical readiness of girls aged 15-17, who go in for Thai boxing, to develop and evaluate the effectiveness of individual pedagogical programs for the correction of lagging physical qualities.
Keywords: Determine the level of physical; fitness of girls 15 - 17 years old; individual pedagogical programs; correction of physical fitness of girls aged